EU Accession: A Boon or Bane for Corruption? - Vincenzo Alfano; Salvatore Capasso; Rajeev K. Goel (Center for Economic Studies and ifo Institute (CESifo), 2020)
The formation and expansion of the European Union (EU) have attracted much attention. However, the impact on the level of corruption in a nation after joining the Union has not been formally studied. Any nation that joins the European Union potentially faces two different and opposite effects on corruption. On the one hand, there are reasons to believe that corruption is going to decrease because of the efforts of the EU to fight corruption or because of the opening of the markets to trade; on the other hand, there are reasons to imagine that corruption may increase due to the increase in bureaucracy and new regulations. Hence, the overall effect is not entirely clear from this perspective. This work focuses on the last three rounds of EU entry and empirically studies the effects of joining the EU on corruption. Placing the analysis in the broader literature on the determinants of corruption, the results suggest that entry into the EU increases corruption. However, equally insightful is that this corruption increase does not hold for nations that are potential entrants or that are in the negotiation stage.
Keywords: D73; E60; F68; K42; 330; corruption; regulations; free trade European Union; joining the EU; EU negotiations; government